Research of The Processes of Wearing the Working Bodies of Road Mills - Askarkhodzhaev, Tulkun Ishanovich; Pirnaev, Sharofiddin Asatullaevich; Mirnigmatov, Batir Tokhta- Muradovich; Abdukarimova, Shohsanam Murodjon qizi (International Journal of Psychosocial Rehabilitation, 2020)
This article is written about the study of the processes of depreciation of the working bodies of road milling machines. The article analyzes the performance, conservation and extension of the working bodies of road milling machines and the calculations of prolonging their effective operation.